3D Tele-Medical Speech Therapy using Time-of-Flight Technology - Stürmer, Michael; Maier, Andreas; Schaller, Christian; Soutschek, Stefan; Penne, Jochen; Handschu, Rene; Scibor, Mateusz; Nöth, Elmar (4th European Congress for Medical and Biomedical Engineering, 2009)
Tele-medical applications allow the treatment of patients over long distances. This is of special importance in speech therapy, since speech therapists often operate in specialized centers for certain disorders. In this paper we propose a novel therapy system which employs Time-of-Flight (ToF) 3D cameras that acquire 3D surface data in real time. The distance data is compressed within a MPEG stream and transmitted to a remote client where a 3D visualization is implemented. The loss in accuracy compared to the original data is within 1.6 mm and 9.7 mm. The system can be used for real-time streaming.
Keywords: Speech Therapy; Time-of-Flight; Telemedicine; MPEG